A very crazy Christmas - Klein, Abby.; McKinley, John, 1956- (New York : Scholastic, 2011)
Freddy tells the story of the Christmas visit of his twin cousins Kelly and Kasey.
450
Accelerated Reader AR
Keywords: Families -- Juvenile fiction; Christmas stories